2019
DOI: 10.1055/s-0039-1683893
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Variances in Patients with Tibial Plateau Fractures

Abstract: Tibial plateau fractures account for approximately 8% of fractures in the elderly population. Treatment strategies in the elderly are similar to those for younger patients; however, practitioners must account for the elevated comorbidity burden in this population. To date, few studies have analyzed age-based outcomes in patients with tibial plateau fractures. Therefore, the purpose of this study was to determine age-related variances in demographics, fracture characteristics, mechanism of injury, and complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
0
20
0
3
Order By: Relevance
“…Lastly, frail elderly patients often have a significant number of comorbidities combined with reduced mobility, which results in a more wait and see attitude. However, as age is not an independent risk facture and elderly patients are not prone to infection [6,10,11]. As the used database is an insurance and cost oriented database, composed and controlled by the government it unfortunately does not allow us to diversify into supplementary data that is of interest to the trauma surgeon (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, frail elderly patients often have a significant number of comorbidities combined with reduced mobility, which results in a more wait and see attitude. However, as age is not an independent risk facture and elderly patients are not prone to infection [6,10,11]. As the used database is an insurance and cost oriented database, composed and controlled by the government it unfortunately does not allow us to diversify into supplementary data that is of interest to the trauma surgeon (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Morbidity increases with the age; malalignment, fracture related infection, non-union, and other postoperative complications, have far-reaching consequences, not only functionally but also financially [4,5]. At long term, post-traumatic osteoarthritis occurs in 25% to 45%, with a 10-year likelihood of 3%-7% for total knee arthroplasty (TKA) and increase of total healthcare costs, subsequently [6]. We recently demonstrated that the rate of surgery for clavicular fractures in Belgium has almost doubled in 10 years, while the indication for this is still under debate [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, to acceptably reduce the joint surface, achieve knee stability and restore the mechanical axis can be challenging due to possible complexity of the fracture or inferior bone quality. ORIF has shown good results in some studies, with low rates (0-9.5%) of complications in older patients [8,9,13,16,17,19]. However, some problems seem to be associated specifically with tibial plateau fractures treated using ORIF.…”
Section: Orifmentioning
confidence: 99%
“…Some studies have found a high risk of complications, such as infections, loss of reduction, malalignment, delayed union or nonunion, and risk for the development of post-traumatic osteoarthritis (OA) [6,[9][10][11][12][13][14][15]. However, many other studies have reported ORIF to have good outcomes in older people [8,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Fractures to the tibial plateau account for approximately 1–2% of all fractures in the general population but for up to 8% of all fractures in the elderly. 1 , 2 While younger patients predominately suffer traffic accidents, high impact sport injuries, or falls from greater height, elderly patients often mainly suffer simple falls or low velocity traumata resulting in a tibial plateau fracture. The loss of bone mass and the deterioration of the bone microarchitecture with age contribute to this change of causal injury mechanism.…”
Section: Introductionmentioning
confidence: 99%